Effects of 1% lidocaine instillation on overactive bladder induced by bladder outlet obstruction in rats - Kang, Hyo Jin; Kim, Sang Woon; Lee, Yong Seung; Han, Sang Won; Kim, Jang Hwan (Urology Journal, 2020)
Purpose: Lidocaine is a common local anesthetic and antiarrhythmic drug that acts via the local anesthetic effect of blocking voltage-gated sodium channels in peripheral neurons. To evaluate lidocaine as a therapeutic agent, we investigated optimal concentrations and effects of intravesical lidocaine instillation in a bladder outlet obstruction (BOO)-induced rat model of overactive bladder (OAB). Materials and Methods: To determine the therapeutic dosage of lidocaine, 16 female Sprague-Dawley (SD) rats (mean weight = 200 ± 20 g) were divided into four treatment groups: those receiving saline, 0.5% lidocaine, 1% lidocaine, and 2% lidocaine (n = 4 per group). Twenty-four additional SD rats were divided into two groups to investigate the effect of 1% lidocaine treatment in rats with BOO and normal rats (n = 12 per group). Cystometry was performed by infusing physiological saline and lidocaine into the bladder at a slow infusion rate (0.04 mL/min). Cystometric parameters were analyzed using PowerLab®. The expression of c-Fos, a protein expressed by C-fibers in the spinal cord (L6), was investigated via western blotting. Results: Among the test lidocaine doses, only 1% lidocaine increased the intercontraction interval (ICI) (control mean = 500.56 ± 24.4 s; treatment mean = 641.0 ± 49.3 s; p < .01) without changes in threshold pressure and basal pressure. In the BOO-induced OAB group, the ICI increased significantly after instillation of 1% lidocaine (control mean = 135.8 ± 12.87 s; OAB-group mean = 274.2 ± 33.21 s; p < .01). Detrusor overactivity and non-voiding contraction were observed in the control group but not in rats with BOO after lidocaine instillation. The expression of c-Fos in C-fibers in the spinal cord (L6) decreased significantly after 1% lidocaine treatment in rats with BOO. Conclusion: Intravesical instillation of 1% lidocaine improves cystometric parameters without deterioration of contractility by blocking excessive C-fiber activity in the rat model of BOO-induced OAB. Therefore, instillation of 1% lidocaine has minimal effects on normal nerves while blocking nerves that contribute to OAB. Our findings suggest that intravesical instillation of 1% lidocaine is a useful treatment for OAB.